Physiological mechanisms of increasing maximal oxygen volume through small sided games training: a systematic review - Muhammad Muhyi; Suharti Suharti; Puspodari Puspodari; Akhmad Syarif; Baskoro Nugroho Putro; Junian Cahyanto Wibawa; Novadri Ayubi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background. An athlete's maximal oxygen capacity, or VO2max, is a crucial measure of their aerobic performance. Since small-sided games (SSG) incorporate tactical, technical, and physical components all at once, they have gained popularity as a teaching tool. According to a number of studies, SSG can raise VO2max by inducing physiological stimuli including elevated heart rate and oxygen consumption. As a result, it's critical to thoroughly examine the physiological processes that underlie the rise in VO2max brought about by SSG training. Objective. This study sought to ascertain whether playing small-sided games increased VO2Max. Materials and methods. For our systematic review investigation, we examined several literature databases, such as Pubmed, Scopus, Web of Science, and Science Direct. We searched for literature published between 2020 and 2025 that discussed VO2Max and small-sided games. Another 664 published papers were found using the databases Scopus, Web of Science, Pubmed, and Science Direct. Ten papers that met the inclusion criteria were selected and reviewed for this systematic review. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were used in this study to assess standard operating procedures. Results. Ten studies that have been examined have demonstrated that training with small-sided games significantly raises VO2Max.